2020
DOI: 10.20471/acc.2020.59.02.12
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the Quality of Public Hospital Healthcare Services by using SERVQUAL

Abstract: hospital healthcare service quality measurement represents an important approach for advancing healthcare systems. This paper presents preliminary results of a research on the quality of healthcare services provided by a large, public, university hospital centre in Croatia, based on the gaps model of Service Quality and the ServQuAl instrument. The importance of particular service quality dimensions was analyzed, as well as the gaps between patient perceptions and expectations of healthcare services provided b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 32 publications
3
12
0
2
Order By: Relevance
“…In addition, as Taner and Antony stated, patients are quite unique as "customers" due to their low expertise and asymmetry of knowledge in comparison with health care professionals [6]. Patients are not skilled and do not have the needed knowledge to diagnose and treat [19].…”
Section: Health Services Qualitymentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, as Taner and Antony stated, patients are quite unique as "customers" due to their low expertise and asymmetry of knowledge in comparison with health care professionals [6]. Patients are not skilled and do not have the needed knowledge to diagnose and treat [19].…”
Section: Health Services Qualitymentioning
confidence: 99%
“…From 700 respondents, 50.6% were males and 49.4% were females. Regarding the age distribution, most of the respondents (29.4%) belonged to the age group of (50-64), 26.1% belonged to the age group of (35-49), 22.4% to the age group of (65 and over) and the remaining 22.0% to the age group of (18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34). In terms of education level, the majority of the participants (36.6%) were university graduates (UG) with or without a postgraduate degree, 33.6% and 14.5% of them reported that they were secondary (SE) and postsecondary education (PSE) graduates respectively, while 15.3% had completed compulsory education (CE).…”
Section: Descriptive Analysis Of the Samplementioning
confidence: 99%
“…Nambisan et al confirmed that responsiveness positively affects patients’ perception of service quality [ 73 ]. In another study in Croatia, the authors highlighted to render quality services, hospital settings should pay more attention to responsiveness compared to other issues [ 74 ]. It is also found that the non-responsiveness of healthcare centers negatively affects the perceived quality by patients [ 75 , 76 ].…”
Section: Theory and Hypothesis Developmentmentioning
confidence: 99%
“…With the change in the medical paradigm and the improvement in the population's standard of living, satisfaction has become one of the critical outcome indicators of healthcare services. It is recommended by the WHO [19,20].…”
Section: Introductionmentioning
confidence: 99%